Spesies Arthropoda Permukaan Tanah Pertanaman Mentimun (Cucumis sativus L.) pada Lahan Bergulma dan Tidak Bergulma - Ririn Nurbandini; Yulia Pujiastuti; Candra Irsan Irsan (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
Weeds always appear in minimal or intensive tillage and cause less optimal growth of cucumbers. This study aims to determine the effect of arthropod diversity on the surface of cucumber plants with weed and non-weed land treatments. The research was conducted in the village of Ujanmas Baru, Muara Enim Regency, South Sumatra. Arthropod observations were carried out using 3 visual methods, pantrap and pitfall traps and the results were analyzed using the calculation of Diversity Index (H'), Individual Distribution (E') and Dominance Index (C). The index obtained in the pitfall traps of the study area with no weeds and weeds in the vegetative and generative phases was categorized in the medium category (H'= 0.56-1.27). The dominant index value of soil arthropods in pitfall traps treated on non-weeds and weeds in the vegetative and generative phases was categorized in the high category range (D = 0.35-0.82). However, in this study the species caught in pan traps were treated on non-weed land and weed land with a diversity index (H') categorized as moderate and a dominant index value (D) categorized as low. The conclusion of this study was that the species of arthropods found in cucumber plants treated with weeds and no weeds did not significantly affect the diversity of arthropods on the cucumber soil surface. Arthropod diversity in cucumber plants in both treatments with pitfall traps and pantrap included in the moderate category with the highest diversity index values of 1.27 and 2.19. Arthropod insect pests found on the surface of the cucumber planting soil consisted of 4 orders and 8 families dominated by Collembola sp and Acheta sp.